Pengaruh Strategi Pemasaran Digital TikTok Shop terhadap Kepuasan dan Keputusan Pembelian Konsumen - Vira Annisa Salsabila (Annusfy : Journal of Multidisciplinary Research, 2026)
This article examines the influence of digital marketing strategies in TikTok Shop on consumer satisfaction and purchasing decisions. It uses a literature review approach, examining recent findings related to content appeal, influencer marketing, live streaming, and digital trust on social commerce platforms. The reviewed studies consistently show that digital marketing elements in TikTok Shop positively influence purchasing decisions, while consumer satisfaction is strengthened by service quality and clear product information. Furthermore, satisfaction plays a crucial role in repeat purchases and consumer loyalty. The findings suggest that the effectiveness of TikTok Shop lies not only in its promotional reach but also in its ability to create an engaging, informative, and trust-building shopping experience. Therefore, businesses using TikTok Shop should prioritize engaging content, responsive communication, credible influencers, and persuasive live shopping sessions to enhance customer satisfaction and purchasing decisions. The article concludes that digital marketing strategies are a determining factor in shaping consumer responses in TikTok Shop-based commerce.